The concept of land resource potential in the economic economy - Chumachenko, O.; Kryvoviaz, Y.; Ostapenko, V. (Land Management, Cadastre and Land Monitoring, 2022)
The article analyzes the conceptual and terminological support in the field of economics of nature management and environmental protection. The need for an in-depth etymological study of the terminological apparatus related to the concept of "land resource potential", namely the concepts of "resource", "potential", "land" in terms of increasing competition among businesses for resources and markets for manufactured products. In this regard, a significant amount of bibliographic and electronic Internet sources, both foreign and domestic authors and researchers. The role of resource potential in the agro-industrial complex of Ukraine is substantiated and determined. The author's interpretation of the concept of "land resource potential" as a set of land, labor, material and economic resources, endowed with the potential for the development of productive forces and characterized by indispensability in the production of dependent and territorially spheres of production. The generalization of concepts is carried out and the mathematical interpretation of the concept "land resource potential" is offered. The establishment of classification features is substantiated and the species classification of resources is carried out. In the course of the research the functional properties of land resource potential were identified and generalized. The role of land resources as one of the main ones in the structure of the nature management system is determined.Key words: land resource potential, land use, nature management, economics of nature management, land.